Bayesian Estimation for the Order of INAR($q$) Model (Communications in Mathematical Research, 2021)
In this paper, we consider the problem of determining the order ofINAR($q$) model on the basis of the Bayesian estimation theory. The Bayesian estimator for the order is given with respect to a squared-error loss function. Theconsistency of the estimator is discussed. The results of a simulation study for theestimation method are presented.